Redesign Jig Side Frame Bogie Lrt Jabodebek - Jovial Auliya Furqan; Alfi Tranggono Agus Salim; Indarto Yuwono; Agung Prasetyo Utomo; Umar Muchtar; Dony Saputra (JMPM (Jurnal Material dan Proses Manufaktur), 2022)
The jig production process at PT IMS focuses on strength, function and production speed. The known problem is the higher strength and cost of producing jigs because the production process is not much at the trial and error stageThis study analyzes the static strength of the jig side frame bogie of the Jabodebek LRT with the parameters of the safety factor and deformation values.Static loading simulation method testing process used is conducted by using Finite Element Method software. It is counted manually to one of conditions to obtain the voltage value compared to the simulation results. This analysis is in form of measured jig design with safety factor and deformation value. The redesigning aim is weight decreasing efficiency. The simulation obtained result in jig early design is the safety factor value 25 and deformation value 0,045 mm. After jig dimension decreasing has been conducted, the redesigning result for safety factor value is 32 and the maximum deformation is 0,114 mm. The results of both simulations are considered as safe because the safety factor values are more than 2 and the deformation value are less than 0,5 mm. Redesigning by decreasing dimension gives better safety factor yet the deformation value increases.